A administração diária do probiótico Lactobacillus paracasei ST11 reduz a letalidade causada por Vaccinia virus em modelo murino - Ana Cláudia dos Santos Pereira Andrade (2015)
Vaccinia virus (VACV), the prototype specie of Orthopoxvirus (OPV) genus, Poxviridae family, played an important role for humanity because of its use during the smallpox eradication campaign. Following smallpox eradication, other OPV have emerging worldwide. VACV is the etiologic agent of the bovine vaccinia (BV), an emerging zoonotic disease that has been associated with economic, social, veterinary and public health issues, especially in Brazil and India. Despite the importance of VB outbreaks there are few therapeutic options available commercially for treatment of OPV infections. In recent years, the probiotic microorganisms utilization has been proposed as a new therapeutic approach for the control of several viral diseases. However, it is unknown the relationship between probiotics microorganisms and poxvirus. This study investigated the effects generated by the daily intake of L. paracasei ST11 in a lethal mice VACV infection. The results showed that treatment using this probiotic after infection with VACV in Balb/c mice was able to decrease the mortality and viral spread. This activity is mediated by the reduction of proinflammatory cytokines such as IFN-γ, TNF-α and IL-17, associated with an increased expression of cytokines with ativiral activity, IFN- α and IFN-β and IFN-λ, in addition of interferon-stimulated genes, OAS and PKR. These results provide information about how probiotics may modulate the host's immune system during VACV infection.